2015
DOI: 10.1111/php.12396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet Radiation (UVA+UVB) and Copper on the Morphology, Ultrastructural Organization and Physiological Responses of the Red Alga Pterocladiella capillacea

Abstract: The effect of ultraviolet (UV) radiation and copper (Cu) on apical segments of Pterocladiella capillacea was examined under two different conditions of radiation, PAR (control) and PAR+UVA+UVB (PAR+UVAB), and three copper concentrations, ranging from 0 (control) to 0.62, 1.25 and 2.50 μm. Algae were exposed in vitro to photosynthetically active radiation (PAR) at 70 μmol photons m(-2)  s(-1) , PAR + UVB at 0.35 W m(-2) and PAR +UVA at 0.70 W m(-2) during a 12-h photocycle for 3 h each day for 7 days. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Due to tidal exposure, intertidal macroalgae are constantly exposed to fluctuating environmental stresses such as high temperature, desiccation and high radiation levels (PAR and UV radiation) (Sampath-Wiley et al 2008) that could easily lead to the formation and accumulation of free radicals and reactive species, triggering oxidative stress. Photobiological studies in macroalgae indicate diverse physiological disturbances in response to UV radiation, including alterations in growth and development (Altamirano et al 2003, Gao and Xu 2008, Navarro et al 2016, pigment degradation (Heo and Jeon 2009), dynamic or chronic photoinhibition of photosynthesis (Barufi et al 2011, Ayres-Ostrock and Plastino 2014, Figueroa et al 2014, protein and DNA damage (Buma et al 2001, Kumar et al 2004, decrease in lipid/fatty acid content (Khotimchenko andYakovleva 2005, Liang et al 2006), inhibition of enzyme activity (Lee and Shiu 2009), alterations in polyamines content (Polo et al 2014b), and modifications in cellular organization and ultrastructure (Holzinger and Lütz 2006, Polo et al 2014a, Schmidt et al 2015. As a photoprotective mechanism against UV radiation, especially UVB, macroalgae can increase the production of UV-absorbing compounds such as mycosporine-like amino acids, phenolic compounds and carotenoids, which play protective roles by mitigating the damage caused by the increase in reactive species (Ruhland et al 2007), therefore giving advantages that enable macroalgae to survive in the presence of UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…brasiliensis exposed to UV-B intensity at 0.35 W/m 2 during 21 days, 3 hours per day [ 32 ]; vegetative thallus of Laurencia catarinenses and Palisada flagellifera treated with UV-B intensity at 0.35 W/m 2 during 7 days, 3 hour per day [ 38 ]; carpospores of Iridaea cordata exposed to three different intensities of UV-B (0.17 W/m 2 , 0.50 W/m 2 , and 0.83W/m 2 ) during 3 days, 3 hour per day [ 15 ]; and tetraspores and early development of Gelidium floridanum exposed to UV-B intensity at 0.12 W/m 2 during 15 days, 2 hour per day [ 2 ]. Changes in chloroplast morphology led to reduction in photosynthetic activity [ 39 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with red algae exposed to ultraviolet radiation, including, for example, Kappaphycus alvarezii (Doty) Doty ex P.C. Silva (Schmidt et al 2010a, b) (Schmidt et al 2015), showed a decrease in level of phycobiliproteins, indicating that UV inhibits synthesis of these pigments.…”
Section: Treatmentsmentioning
confidence: 97%
“…brasiliensis E.C. Oliveira & Coll (Bouzon et al 2012), Gelidium floridanum W.R. Taylor (Simioni et al 2015), and Pterocladiella capillacea (S.G.Gmelin) Santelices & Hommersand (Schmidt et al 2015). In addition to the change in chloroplast morphology, algae exposed to PAB radiation also showed an increase in the number of plastoglobuli in the chloroplasts.…”
Section: Treatmentsmentioning
confidence: 99%